2015
DOI: 10.1097/ijg.0b013e318287abf3
|View full text |Cite
|
Sign up to set email alerts
|

Role of Subconjunctival Bevacizumab as an Adjuvant to Primary Trabeculectomy

Abstract: Although subconjunctival bevacizumab is effective and safe in primary trabeculectomy, IOP control appears to be superior with MMC, in terms of complete success with a target IOP<12 mm Hg and number of antiglaucoma medications required postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 40 publications
1
56
2
3
Order By: Relevance
“…However, the success rate of this surgery has been limited by postoperative fibroblast proliferation and scarring of the filtering bleb. 1 Numerous adjunctive modifications, such as antimetabolites, 2 b-radiation, 3 and anti-VEGF agents, 4 have been developed to prevent scarring.…”
Section: Introductionmentioning
confidence: 99%
“…However, the success rate of this surgery has been limited by postoperative fibroblast proliferation and scarring of the filtering bleb. 1 Numerous adjunctive modifications, such as antimetabolites, 2 b-radiation, 3 and anti-VEGF agents, 4 have been developed to prevent scarring.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of anti-VEGF, recent studies question their effectiveness. Thus, according to Akkan and Cilsim, bevacizumab achieved a lower IOP reduction and an increased incidence of encapsulated blebs 1 year after trabeculectomy [31] . In the case of the amniotic membrane, its use has not been extended despite its promising results [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab was identified as a potential agent in conjunction with trabeculectomy [7,22,23]. However, bevacizumab alone may not be as effective as MMC in the long-term control of IOP [11,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The stricter criteria of success in the Vandewalle et al [15] study may have contributed to more office-based interventions, such as early postoperative bleb massage and suture lysis, to fulfill their criteria of success. A previous meta-analysis [11], which included trials by Akkan and Cilsim [22] and Pro et al [23], showed that MMC usage resulted in significantly better control of IOP than anti-VEGF antibodies at the 12-month follow-up [11,22,23]. Of note, Nilforushan et al [24] reported that MMC offered better control of IOP than bevacizumab alone at the 1-month (p < 0.001) and 6-month (p = 0.003) follow-ups.…”
Section: Discussionmentioning
confidence: 99%